The Effect of Corporate Announcements on Insurance Stock Prices in Nepal - Adhikari, Chandra Prasad (Medha: A Multidisciplinary Journal, 2026)
This study examines how dividend announcements affect the stock prices of life insurance companies in Nepal. To do this, this study takes two main companies: Nepal Life Insurance Co. Ltd. (NLIC) and National Life Insurance Co. Ltd. (NLICL). These two are taken because their dividend amounts differ significantly. NLIC offered a high payout of 21.05%, while NLICL offered a lower payout of 12.50%. This study uses daily stock prices and the NEPSE index for the 10 days before and after news announcements in 2024 and 2025. The data shows that these announcements definitely move the market. On the day the news came out, NLIC’s stock jumped with a gain of 2.17% above the market, while NLICL had a smaller gain of 0.97%. A major finding is that high dividends keep investors interested for a long time. For the smaller dividend, people tended to sell their shares quickly to make a fast profit. Also, because prices started rising a few days before the official announcement, it seems the market is not perfectly efficient, and news might be leaking out early. This study is helpful for regular investors, policymakers, government agencies, insurance companies, etc., in Nepal who want to know the best time to buy or sell insurance stocks.